Dual-responsive nanoparticles targeting ACE-II senescence for therapeutic mitigation of acute lung injury - Linlin Gao; Fushuang Zheng; Zhiling Fu; Wei Wang (Journal of Nanobiotechnology)
Abstract Acute lung injury (ALI) is a life-threatening condition characterized by severe pulmonary dysfunction, with alveolar type II epithelial cell (ACE-II) senescence playing a pivotal role in its progression. In this study, we developed pH/reactive oxygen species (ROS) dual-responsive nanoparticles (GNPsanti-SP-C) for the targeted delivery of Growth Differentiation Factor 15 (GDF15) to counteract ACE-II senescence. These nanoparticles (NPs) effectively activate the AMP-activated protein kinase (AMPK)/Sirtuin 1 (SIRT1) signaling pathway, inducing the mitochondrial unfolded protein response (UPRmt) and reversing senescence-associated cellular dysfunction. GNPsanti-SP-C were systematically engineered and demonstrated robust pH/ROS sensitivity, efficient GDF15 release, and precise ACE-II targeting. In lipopolysaccharide (LPS)-induced ALI mouse model, GNPsanti-SP-C treatment significantly mitigated lung injury, reduced inflammatory responses, and enhanced pulmonary function, as evidenced by decreased inflammatory markers, lung edema, and improved histopathology. Single-cell transcriptomic and proteomic analyses revealed increased ACE-II cell populations, reduced expression of senescence markers, and upregulation of AMPK/SIRT1 signaling. In vitro studies further demonstrated that UPRmt activation is associated with the NPs’ therapeutic effects, suggesting a potential role in their mechanism of action. These findings demonstrate the potential of GDF15-loaded dual-responsive NPs as an innovative strategy to address cellular senescence and alleviate ALI-associated pulmonary damage. Graphical abstract